Retinal Protective Effect of Mono-Ethyl Fumarate in Experimental Age-Related Macular Degeneration via Anti-Oxidative and Anti-Apoptotic Alterations - Lee, Hara; Zhang, Siqi; Ahn, Hong Ryul; Kim, Taejung; Kim, Jiyool; Lee, Heesu; Jung, Sang Hoon; Kim, Joonki (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Age-related macular degeneration (AMD) is a leading cause of vision impairment in people over the age of 60. Currently, the FDA-approved drugs for AMD have various side effects, and there is a notable lack of drug development for dry AMD. This study aimed to explore the therapeutic effects of mono-ethyl fumarate (MEF) on AMD. MEF effectively protected ARPE-19 cells from cell death induced by a combination of A2E and blue light exposure. In a C57BL/6J mouse model of retinal degeneration caused by sodium iodate, MEF played a role in preserving retinal thickness and maintaining the layered structure of the retina. It was assessed via fundus imaging, optical coherence tomography, and hematoxylin and eosin staining. Treatment with MEF significantly increased the expression of antioxidant proteins such as HO-1, NQO1, and SOD1 in ARPE-19 cells. Additionally, treatment with MEF significantly increased the levels of the antioxidant proteins SOD1 and GPX4 in the mouse retina. Concurrently, it significantly reduced the levels of apoptosis-related factors, such as the Bax/Bcl-2 ratio and Caspase -3 cleavage. These findings suggest that MEF may represent a promising therapeutic candidate for the management of AMD.